Ganti Rugi Akibat Klausula “Memecahkan Berarti Membeli” di PT. Alaska Mandiri Cemerlang Kota Makassar: Studi Komparatif Mazhab al-Syafi’i dan Mazhab Hambali - Ramdani, Rinto; Asti, Mulham Jaki (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This research is entitled "Comparative Study of the Syafi'i School with the Hambali School of Compensation Due to the "Solving Means Buying" Clause (Case Study of PT Alaska Mandiri Cemerlang Makassar City)", The problem is divided into several sub-problems, namely: 1) How is the problem solving process if there is an accidental breakdown of goods due to standard clauses in the perspective of the Shafi'i school and the Hambali school? 2) How do the views of the Shafi'i and Hambali schools compare regarding compensation due to the clause "to solve means to buy." The results of this study indicate that: 1) At PT Alaska Mandiri Cemerlang Makassar City in the application of the standard clause "Solving Means Buying" has been very good because all parties from Managers, employees, security and others provide good service to consumers who come shopping, when there are consumers who accidentally damage goods, then PT Alaska Mandiri Cemerlang Makassar City will provide a good explanation and understanding so that consumers can accept them well, admit their mistakes and be responsible for their mistakes by compensating for the goods that have been damaged, 2) Compensation in the standard clause “to solve means to buy” at PT Alaska Mandiri Cahaya, Makassar City, is said to be valid in the view of the Syafi'i and Hambali schools because the pillars and conditions have been fulfilled. The Shafi'i School and the Hambali School both agree that when someone damages someone else's property, they are obliged to compensate if they do not compensate it will be worth a sin for him.